SURVEILLANCE OF PARASITIC DISEASES IN BULGARIA - Rumen Harizanov; Violeta Yakimova; Mihaela Videnova; Ognyan Mikov; Aleksandra Ivanova; Eleonora Kaneva; Raina Borisova; Nina Tsvetkova; Iskra Rainova; Zornitca Traykova (Problems of Infectious and Parasitic Diseases)
The incidence and number of cases of several parasitic diseases subject to mandatory reporting and registration under the Ministry of Health (MoH) 2005 Regulation 21 increased after the end of the global pandemic of COVID-19 in 2023. In addition, parasitic infections imported from endemic tropical regions are recorded annually in the country. A significant number of people are screened for parasitic diseases each year. The primary indication for screening is prophylactic, followed by epidemiological and clinical indications. This report aims to analyse the dynamics of parasitic diseases in 2023. Data from the periodic and annual reports of the RHI, medical institutions and NCIPD were used as inputs. In 2023, 647 781 people were tested for parasites, of whom 2.0% were diagnosed with various parasitic infections. Cystic echinococcosis increased from 89 cases in 2022 to 117 cases in 2023. The annual incidence of the disease increased from 1.3% in 2022 to 1.81% in 2023.